Customer vs Citizens: Memperkuat Positioning Mahasiswa dalam Manajemen Pelayanan dan Reformasi Birokrasi Perguruan Tinggi Islam - M. Rosyid Ridla; Bayu Mitra A. Kusuma; Munif Solikhan (Institut Agama Islam Negeri Bengkulu, 2021)
The term world class university is becoming a trending topic in the tertiary education environment in Indonesia. Not wanting to be left behind in these carriages, Sunan Kalijaga State Islamic University in Yogyakarta has declared itself to be a world class university in Islamic studies. The ideal position continues to be socialized to the entire academic communities. One of the study programs that take the vision seriously is the Da'wah Management Study Program under the auspices of the Da'wah and Communication Faculty. This study program continues to boost efforts to internationalize institutions through a variety of academic and collaborative activities. But the question is whether the external strengthening has been balanced with internal reinforcement, in this case the service management and the campus bureaucratics reform. Based on this, further questions arise about how students' positions as service users, are treated as customers or citizens. This research uses a qualitative method and a descriptive approach. The results of comparative analysis based on New Public Management and New Public Service theories show that in service management and bureaucratic reform in the Da'wah Management Study Program, students are treated more as citizens, not as customers. This can be seen from several points of findings such as: (1) services are not based on individual interests, but overall students are based on the principle of equality, (2) service delivery is conducted in a fair manner in this case not interpreted as equal to absolute, but in accordance with conditions and needs or prioritizing inclusiveness, (3) service is not market-oriented where study programs open as wide a negotiation space as possible for each student interest, provide access and response to various student complaints, and (4) pay attention to multiple aspects of service such as accountability in law, community values, political norms, professional standards, and fulfilling the interests of students as citizens.